Development Research on Integrating CNC Machine Tool with Plasma for Online Surface Heat Treatment. (16th October 2021) - Chen, Shao-Hsien; Wang, Bo-Ting
Abstract : In this study, the plasma was integrated with a lathe, and the online heat treatment was performed to achieve mechanical strength and hardness, to reduce the machining process and handling. However, for online heat treatment of cast iron FC25, it is important to study the parameters of the lathe and plasma, and the research method is used eventually to optimize the process and reduce the machining cost and machining error. The variable factors in the surface online real-time heat treatment are spindle speed, feed rate, and current, and the objective function is the hardness of mechanical properties. In the screening experiment, the interaction of factors was discussed using a full factorial experiment. The Central Composite Design was combined with the Lack-of-Fit test for the optimization experiment, and the R 2 coefficient was used to determine whether the regression model is appropriate. The optimum parameters were derived from the contour diagram and response surface diagram. The experimental results show that the significant factors include spindle speed, feed rate, and current and the optimum parameters include spindle speed of 168 rpm, feed rate of 0.068 mm/rev, and current of 86 A. The experimental results of optimum parameters show that the surface hardness is increased from 306 HLD to 806 HLD and the surface hardening effect is enhanced by 163%, so the online real-time heat treatment equipment has the best hardening effect.